173k views
5 votes
Simplify the following? (x^4y)^3

User Aditzu
by
6.3k points

2 Answers

3 votes

Answer:

(x^12y)

Explanation:

= (x^4y)^3

= (x^12y)

User Lachie
by
6.3k points
3 votes

Answer:

The simplified form of given expression is x¹²y³

Explanation:

Points to remember

Identities

(xᵃ)ᵇ = xᵃᵇ

xᵃ * xᵇ = x⁽ᵃ ⁺ ᵇ⁾

To find the simplified form

It is given that, (x⁴y)³

By using the above identities we can write (x⁴y)³ as,

(x⁴y)³ = (x⁽⁴ * ³ ⁾ * y³

= x¹² * y³

= x¹²y³

Therefore the simplified form of given expression is x¹²y³

User Edmond Wang
by
5.8k points